MORAL DEVELOPMENT IN PSYCHOLOGICAL PERSPECTIVE - Thomas, T. M. (Journal of Dharma, 1979)
Morality has been traditionally considered a philosophical and religious question, and sciences Were regarded as amoral. But today, with the increased emphasis on the human relevance of sciences in general and the great advances made in human sciences like psychology and. sociology; the role of these sciences in defining the moral dimension of human life has assumed greater importance. .Many psychologists,' in spite of their differences in presuppositions and orientations, have undertaken the study of morals using a' scientific approach. Cognitive developmental psychologists like Piaget and Kohlberg are widely known for their contributions in the area of moral development. Social learning theorists show that moral behaviour is expressed by each person as a result of imitation of other people. Prior to the acceptance of both these theories Freud stirred the moral issue by introducing the concept of conscience giving it a new meaning. , In this paper I shall indicate the approach to moral development.by these three schools and discuss their relevance to the wider question of morality.